Determinación de la agresividad de la precipitación en la parte alta de la cuenca del Río Pastaza, en el periodo 1976 – 2000 - Andrade Melendres, Jessica Tatiana (2021)
The increase in the aggressiveness of precipitation is a critical problem in many upper basins of the world, since this phenomenon causes the loss of nutrients, soil erosion, sedimentation in the middle and lower part of the basin. The objective of this research is to determine the aggressiveness of precipitation in the upper basin of the Pastaza river, this basin was considered since it represents the agricultural sector with the highest production in the country. Monthly rainfall data was selected from 21 meteorological stations for the period 1976-2000. To determine the spatio-temporal aggressiveness of the precipitation, the Fournier indices, Modified Fournier, Kriging interpolation method, Weighted Inverse Distance were used. Also, the aggressiveness trend analysis was performed using the Mann-Kendall non-parametric statistical test. The results of this study show aggressiveness of the average annual precipitation of very low, low and moderate, the provinces of Cotopaxi and Tungurahua present annual average values lower than 100 and 200, which indicates very low and low levels of water erosivity. It should be noted that the Licto and Cajabamba areas belonging to the province of Chimborazo located to the south of the basin at an altitude of 3,160 and 2,840 meters above sea level have moderate aggressiveness levels with values higher than 200, which shows trends of high erosivity of precipitation be it with the passage of time, climate change, topography, agricultural activities or other factors. In addition, this research has environmental, social and economic impacts, which are subject to the conservation, planning, zoning and remediation of soil and water resources. The climatic aggressiveness indices allow us to quantitatively determine the possible impacts of precipitation on the soil and identify the areas of less and greater erosivity, through the analysis it gives us the possibility of seeking comprehensive soil resource management strategies for a sustainable world.